Antibodies to lens antigens in cataract and after cataract surgery. Issue 1 (January 1981) - Nissen, S. H.; Andersen, P.; Andersen, H. M.
Abstract : By means of an enzyme-linked immunosorbent assay (ELISA) antibodies to whole lens homogenate were found in 50.0% of 38 patients with senile cataract and in 57.3% of 75 controls. The antibody titres were in the range of 10-160 in both groups. IgG antibodies occurred in 44.7% of patients and in 45.3% of controls, whereas IgM antibodies were found in 21.1% of the patients and in 40.0% of the controls (not significant). Postoperative uveitis occurred in 5 (31.6%) of 19 patients, who had antibodies in serum prior to the operation and in only 2 (10.5%) of 19 antibody-negative patients (P = 0.10).